Tunable dual-functional metasurface for wideband cross-polarization conversion and wideband absorption - Chandu DS; K.B.S. Sri Nagini; Ping Jack Soh; S.S. Karthikeyan (Results in Physics, 2023)
This work presents a tunable and wideband dual-functional metasurface (DFM) operating in the terahertz regime with highest overlap bandwidth (OBW). The structure consists of a double-split ring resonator and a meandered square ring resonator based on VO2 to achieve reflective cross-polarization conversion and absorption functionalities, respectively. When the phase changing material VO2 is in its metallic state, the metasurface acts as a perfect absorber with a peak absorption of ≥ 90% over the operating band of 2.3–4.01 THz. When VO2 is in its insulating state, the metasurface acts as a reflective cross-polarization converter over a wideband from 1–4.1 THz with high polarization conversion ratio of ≥ 90%. The proposed DFM has a stable response up to 45∘ of incidence in the polarization converter state and 60∘ of angular stability under the absorber state. Further, tunability is achieved by integrating photoconductive silicon and controlling the optical pump intensity in the double-split ring and meandered . square ring resonators. The proposed metasurface finds its applications in security, detection and THz communication systems.